Adsorption and anti-corrosion properties od cuttingfluids for shear blades of glass-forming machines - Ponomarev Daniil Andreevich; Marina Pavlovna Krasnovskikh; Solovyova Anastasia Dmitrievna; Shcherban Marina Grigorievna (Zaštita Materijala)
The article presents the studies on the adsorption of water-miscible oil-containing cutting fluids on the R6M5 high-speed steel surface. The fluids can be used for the shear blades of drop feeders in glass-forming machines. The dependence of the anti-corrosion and lubricating properties of cutting fluids on their adsorption on steel surfaces is determined. The survey shows the serial G-417 cutting fluid achieves the highest adsorption value and anti-corrosion effect at a volumetric dilution of 1:4000, compared to the experimental cutting fluid based on G-417 at 1:1500. Based on the tests of the experimental cutting fluid at a glass factory, the experimental lubricant has greater operating dilution (1:1300) compared to the G-417 (1:800) at the same initial oil content. The higher lubricity of the new cutting fluid can be explained by the position of the adsorption maximum for the experimental mixture. The research formulates a necessary condition for improved operating characteristics, lubricity, and anti-corrosion properties of a cutting fluid by the selection of emulsifiers and functional additives for the cutting fluid: the proximity of the concentrations for maximum adsorption capacity and operating dilution ranges (1:800 - 1:2000). Electrochemical studies show that both the G-417 and experimental lubricant have anodic mechanism of corrosion inhibition